Forging enmities and friendships: Europarties, electoral coalitions and mergers in Central and Eastern Europe. (January 2020) - Ibenskas, Raimondas
The inability of Europarties to provide the electoral linkage between citizens and policymakers is a key challenge for the European Union. However, relatively young and unstable parties and party systems in Central and Eastern Europe (CEE) present greater opportunities for the Europarties to impact electoral politics in this region. This research examines the influence of the most established Europarties on electoral coalitions and mergers among CEE parties. A cross-national comparative analysis of 11 CEE countries in the first two decades after their democratic transitions suggests a moderately strong effect of the Europarties. Europarties facilitate mergers of their member or potential member parties and prevent electoral coalitions between their member and potential member parties and radical left and right parties.